HUBUNGAN ANTARA ASUPAN MAKAN, STATUS GIZI, DAN KELELAHAN KERJA TERHADAP PRODUKTIVITAS KERJA PADA PEKERJA PABRIK PT. TIGARAKSA SATRIA Tbk. YOGYAKARTA - , MARSELLA MAHARDHIKA DEWI; , Yayuk Hartriyanti, SKM, M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Nowadays, many factories strive for having healthy and productive labour to compete with another factories. However, many factories havenât provided yet health service for their labour properly. It may cause decreasing of labourâs productivity. Some researches found that healthy level of labour is related to their productivity. Objective: To determine the correlation between dietary intake, nutritional status, occupation fatigue, and work productivity at Tigaraksa Satria labour, Yogyakarta. Method: This research was a cross sectional study and located at Tigaraksa Satria Yogyakarta during October 2012-Februari 2013. This subjects were production at Tigaraksa Satria labour, Yogyakarta that amounted to 72 people. Data were collected by using questionnaires food recall 24 hours and KAUPK2, interview method, and antropometric measurements. Data were processed and analyzed by using Pearson Correlation with Chi square test. Result: Statistical analysis showed that there was no significant correlation between dietary intake and nutritional status (p > 0,05). There was no significant correlation between dietary intake and occupation fatigue (p > 0,05). There was also no correlation between nutritional status and occupation fatigue (p > 0,05). There was no correlation between occupation fatigue and work productivity (p > 0,05). Conclusion: There is no correlation between dietary intake, nutritional status, occupation fatigue, and work productivity among labour at Tigaraksa Satria Yogyakarta.